Gold Electrodes Modified with Self-Assembled Layers Made of Sulphur Compounds and Gold Nanoparticles Used for Selective Electrocatalytic Oxidation of Catecholamine in the Presence of Interfering Ascorbic and Uric Acids - Teresa Łuczak (International Journal of Electrochemistry)
Gold electrodes modified with S-containing compounds and gold nanoparticles were used for determination of epinephrine (EP) in aqueous solution. The modified electrodes exhibited a good sensitivity, reproducibility, and stability. The results have shown that modified electrodes could clearly resolve the oxidation peaks of epinephrine, ascorbic acid (AA), and uric acid (UA) with peak-to-peak separation enabling determination of EP, AA, and UA in their simultaneous presence. A linear relationship between EP concentration and current response was obtained in the range of 0.1 μM to 700 μM with the detection limit ≥0.034 μM for the electrodes modified at 2D template and in the range of 0.1 μM to 800 μM with the detection limit ≥0.030 μM for the electrodes modified at 3D template.